Dyskurs edukacyjny na lekcji języka obcego w polskim liceum a brytyjskim The Sixth Form College – wyniki badań porównawczych - Kouhan, Beata (Neofilolog, 2019)
Examining different solutions implemented during foreign language lessons in different countries can be very useful. Firstly, noticing some innovative ideas in an authentic context in another educational system can inspire the introduction of some changes which can potentially raise the quality of foreign language in-struction. Secondly, seeing the same solutions in another educational system can confirm the effectiveness of existing methods and in this way may strengthen the intrinsic motivation of all involved in the teaching process of teaching for-eign languages. One of the most important elements of a foreign language les-son is educational discourse taking place in the classroom as it has the potential to affect all aspects of a particular class and to greatly influence learning out-comes. With this in mind, the author included educational discourse in a com-parative study of the processes taking place during foreign language lesson in two types of schools: the Polish upper secondary school and the British sixth form college. The article is divided into four sections. The first one deals with the literature related to discourse, especially discourse in education. In the sec-ond section, the structure and the scope of the research will be presented, in-cluding the research tools, the subjects of the study, the research questions, the scope and the organisation of the activities, and the factors potentially limiting and influencing the outcomes of the research. In the third part, the results of the study will be presented on the basis of the analysis of the data collected by means of questionnaires, observations and interviews. In the final section, the author will draw conclusions and make some pedagogical recommendations.